Beyond words: investigating non-verbal indicators of collaborative engagement in a virtual synchronous CSCL environment - Jeitziner, Loris T.; Paneth, Lisa; Rack, Oliver; Zahn, Carmen (Frontiers in Psychology, 2024)
In the future of higher education, student learning will become more virtual and group-oriented -and this new reality of academic learning comes with challenges. Positive social interactions in virtual synchronous student learning groups are not self-evident -but need extra support. To successfully support positive social interactions, the underlying group processes, such as collaborative group engagement, need to be understood in detail, and the important question arises: How can collaborative group engagement be assessed in virtual group learning settings? A promising methodological approach is the observation of students' nonverbal behavior, for example in videoconferences. In an exploratory field study, we observed the nonverbal behavior of psychology students in small virtual synchronous learning groups solving a complex problem via videoconferencing. The groups were videorecorded to analyze possible relations between their nonverbal behaviors and to rate the quality of collaborative group engagement (QCGE). A rating scheme consisting of four QCGE dimensions (Behavioral, Social, Cognitive, Conceptual-toconsequential QCGE) was applied and nonverbal behaviors during the task were coded based on related research literature. We quantitatively and qualitatively analyzed nonverbal behaviors as indicators of QCGE. The results show that groups use a wide range of nonverbal behaviors. Furthermore, certain nonverbal behaviors are significantly related to specific dimensions of QCGE. These results help to identify relevant indicators of QCGE in virtual synchronous learning settings and thus promote the development of advanced methods for assessing QCGE. Furthermore, the indicators can be discussed as possible anchors for supporting collaborative learning in virtual synchronous groups.